Toxicity of lead bioaccumulation and its effects on liver, kidney and blood functions in laboratory rats - Saeda Maatoq Ali; Masoud Abo- sathi (African Journal of Advanced Pure and Applied Sciences, 2026)
This study aimed to determine the bioaccumulation of lead and its effects on blood, liver, and kidney function. The study included 40 male mice. The mice were divided into four groups. They were given intraperitoneal doses of lead daily for 4 weeks. as follows: Control group G1 received distilled water throughout the experiment, Group G2 was injected with a dose of lead of 10 mg/kg-1 .b. w, Group 3G was injected with 50 mg/kg-1.b. w, group G4 was injected with 100 mg/kg-1b. w, after 4 days from the end of the experiment, blood samples were collected and serum was obtained to measure hematological parameters and liver and kidney functions. The results of blood parameters showed a significant decrease (P< 0.05) in the rate of WBC, RBC, HB, HCT higher the lead dose compared to the control group. While MCV, PLT decreased at concentration 100 mg/kg-1. b. w, While the dose of 10 and 50 mg/kg-1 .b. w has the same effect. results showed a significant increase (P< 0.05) in the levels of AST, ALT, ALP, bilirubin, creatine, urea, and urea acid. The higher the lead dose. While Total protein recorded a significant decrease (P< 0.05) the higher the lead concentration. As for the electrolytes results, the results showed that the groups that took a concentration of 10 and 50 mg/kg-1. b.w, had the same effect on the potassium level, While the group that took dose 100 mg/kg-1 increased the potassium level compared to the control group. The results showed a significant decrease in calcium and magnesium levels with increasing lead concentration compared to the control group. While sodium recorded a significant increase at concentrations of 1.100 mg/kg-1. Lead levels were assessed in kidney, liver, and blood tissues, and the results showed that lead levels increase with increasing dose.